ANALISIS KEBIJAKAN PENGELOLAAN SAMPAH DI PASAR MINGGU KOTA BENGKULU - Nanda, Nanda; Rosidin, Rosidin (Yayasan Insani Mandiri Santani, 2024)
This research began with the fact that there was still a lot of rubbish found on the side of the road near the Sunday market, of which, if left to continue, it would give rise to germs of disease, unpleasant odors, and environmental pollution would cause disasters such as floods. This research uses a qualitative analysis approach with descriptive methods. The use of this descriptive method is based on a problem solving procedure by describing the current state of an object or subject based on facts. The approach used is a qualitative approach. By using the theory of Policy Implementation from George Edward III which suggests that Policy Implementation can be determined by 4 factors, namely Communication, Resources, Disposition and Bureaucratic Structure. The results of the research show that the implementation of waste management policies in Pasar Minggu has not been running optimally, this is indicated by the lack of quality human resources who can manage waste into more useful and reusable goods, the lack of the required fleet and the absence of standards. Operational Procedures (SOP) in implementing policies so that policy implementers and related parties only carry out instructions from the Government. The thing that is an obstacle in implementing policies at Pasar Minggu is the lack of awareness among the people of Pasar Minggu about the importance of protecting the surrounding environment and the bad habits of